BARTHES’ SEMIOTIC ON THE GIANT COCKROACH IN “THE METAMORPHOSIS” BY FRANZ KAFKA - RAHMAN, MAUFIQUR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: Barthes, Semiotic, cockroach. This research is aimed to know the significations behind the giant cockroach in “The Metamorphosis” by Franz Kafka based on Barthes’ semiotic perspective. In Barthes’ semiotic, the signification does not stop at the signifier and signified meaning but it continues to the meta-language meaning; myth. Then, this signification is called as the second order of signification. Cockroach is signifier and disgusting animal is the signified. In the first order of signification, cockroach denotes a disgusting animal. Inthis case, cockroach is not only viewed as a disgusting animal but beyond that, because Gregor’s transformed into disgusting animal which leads to him to be avoided by his family and society. His family avoids him because he cannot work again. Gregor isolated from the other after the transformation is the second order of signification.This research finds many clues in the novella that Gregor’s transformation symbolizes something else. As cockroach, Gregor dislikes milk and prefers to eat spoiled food means he can survive in in different way. Gregor dislikes what people usually like and Gregor needs what usually people do not need. It means the tolerance is important thing in real life because the difference is a certainty. Gregor sleeps under the chairmeans his father’s pressure for a long time makes him weak. His weakness relates to the sofa or chair that also means power. Indeed, Gregor’s conflict with his father makes him lose his power in his family. This behavior also means that Gregor has closed-personality and feelings, which Gregor always hides under it. Crawling all over the room means that he cannot be stagnant and he entertains himself to forget his nightmare and his suffering for a moment. Then, the impact of the transformation makes Gregor to be isolated from his job, his family, and even from his own thought. Gregor’s death is a way to escape from his strangeness and suffering.